2015
DOI: 10.1016/j.jhealeco.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Affordable Care Act dependent coverage provision on health-related outcomes of young adults

Abstract: The first major insurance expansion of the Affordable Care Act - a provision requiring insurers to allow dependents to remain on parents' health insurance until turning 26 - took effect in September 2010. We estimate this mandate's impacts on numerous outcomes related to health care access, preventive care utilization, risky behaviors, and self-assessed health. We estimate difference-in-differences models with 23-25 year olds as the treatment group and 27-29 year olds as the control group. For the full sample,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(91 citation statements)
references
References 65 publications
8
83
0
Order By: Relevance
“…The findings of this paper are not surprising since the health status of those with relatively low risk of having health problems (those who are around the age 19 cutoff) are not likely to change in the shortrun. The results of this paper are also comparable to several recent studies, who argue that risky health behaviors among young adults might be relatively difficult to improve through access to health care since they require significant life style changes (Barbaresco et al 2015;Finkelstein et al 2012).…”
Section: Resultssupporting
confidence: 86%
“…The findings of this paper are not surprising since the health status of those with relatively low risk of having health problems (those who are around the age 19 cutoff) are not likely to change in the shortrun. The results of this paper are also comparable to several recent studies, who argue that risky health behaviors among young adults might be relatively difficult to improve through access to health care since they require significant life style changes (Barbaresco et al 2015;Finkelstein et al 2012).…”
Section: Resultssupporting
confidence: 86%
“…Some of the most recent papers [Akosa Antwi et al 2015;Barbaresco et al 2015;Depew and Bailey 2015], in part because of the influence of early versions of this paper, do use placebo tests or reduced-age bandwidths (or both). Their conclusions of positive impacts on having a usual source of care, self-reported health, less-delaying care because of cost, increased inpatient admissions, and premium increases are therefore likely robust.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent papers study the potential effects of this early provision, making important contributions. Their results are intuitive: an increase in the share of individuals with dependent insurance coverage [Cantor et al 2012b;Sommers and Kronick 2012;Akosa Antwi et al 2013;O'Hara and Brault 2013;Sommers et al 2013;Chua Sommers 2014], a decrease in the uninsurance rate [Cantor et al 2012b;Sommers and Kronick 2012;Akosa Antwi et al 2013;Mulcahy et al 2013;O'Hara and Brault 2013;Jhamb et al 2015], a decreased likelihood of delaying or not obtaining care because of cost , Barbaresco et al 2015, a decrease in out of pocket costs [Chua and Sommers 2014;Busch et al 2014] an increased likelihood of having a usual source of care ; Barbaresco et al 2015], increased labor market flexibility [Akosa Antwi et al 2013], a drop in share of uninsured emergency room (ER) visits [Mulcahy et al 2013], improved self-reported health [Carlson et al 2014; Barbaresco et al 2015], increased use of inpatient and mental health resources [Saloner and Lê Cook 2014;Akosa Antwi et al 2015], an increase in dental coverage [Han et al 2014;Shane and Ayyagari 2015], a decrease in ER visits [Hernandez-Boussard et al 2014;Akosa Antwi et al 2015], and increase in premiums for health insurance plans that cover children [Depew and Bailey, 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Urban Institute and Georgetown researchers noted, reductions in uninsurance among children began well in advance of the ACA, but new public and private insurance options for adults have had a strong “spillover effect” on continued coverage and access improvements for children [15,20]. With respect to ACA impacts on young adults, published studies based on the American Community Survey, the Medical Expenditure Panel Survey, and NHIS data have documented solid reductions in uninsurance and mixed effects related to access to care associated with expansions in dependent private coverage, Medicaid, and non–group insurance through marketplace exchanges [16,21,22,26]. …”
mentioning
confidence: 99%